Exploring tacit knowledge transfer and innovation capabilities within the buyer–supplier collaboration: a literature review - Shem Sikombe (Taylor & Francis Group, 2019)
The study seeks to identify the main facilitators and barriers of tacit knowledge transfer that influence innovation capabilities of the supplier within the buyer–supplier collaboration.The conceptual paper is based on a systematic literature review of 23 peer reviewed journal articles from Elsevier/Science Direct, Emerald, Springer and Scopus. Literature related to buyer–supplier context, tacit and explicit knowledge transfer, knowledge management for innovation purposes was reviewed and synthesised. Findings of the study indicate that organisational contextual factors, relationship strength, internal knowledge brokers, communication and transparency and link duration positively support tacit knowledge transfer and innovation. Complementarity of skills act as a barrier to operational knowledge transfer; however, it supports learning leading to supplier development and innovation in new product development. Conversely, knowledge stickiness is cited as a barrier to tacit knowledge transfer after reaching diminishing returns. The study synthesises the main facilitators of tacit knowledge transfer for managers/practitioners to consider in the buyer–supplier collaboration which can influence supplier innovation on projects such as new product development. The study has further proposed a model that will be tested quantitatively in the subsequent empirical study.